Multi-center implementation of rapid whole genome sequencing provides additional evidence of its utility in the pediatric inpatient setting - Thompson, Lauren; Larson, Austin; Salz, Lisa; Veith, Regan; Tsai, John-Paul; Jayakar, Anuj; Chapman, Rachel; Gupta, Apeksha; Kingsmore, Stephen F.; Dimmock, David; Bedrick, Alan; Galindo, Maureen Kelly; et al. (Frontiers in Pediatrics, 2024)
Multi-center implementation of rapid whole genome sequencing with assessment of the clinical utility of rapid whole genome sequencing (rWGS), including positive, negative and uncertain results, in admitted infants with a suspected genetic disease.rWGS tests were ordered at eight hospitals between November 2017 and April 2020.Investigators completed a survey of demographic data, Human Phenotype Ontology (HPO) terms, test results and impacts of results on clinical care.A total of 188 patients, on general hospital floors and intensive care unit (ICU) settings, underwent rWGS testing. Racial and ethnic characteristics of the tested infants were broadly representative of births in the country at large. 35% of infants received a diagnostic result in a median of 6 days. The most common HPO terms for tested infants indicated an abnormality of the nervous system, followed by the cardiovascular system, the digestive system, the respiratory system and the head and neck. Providers indicated a major change in clinical management because of rWGS for 32% of infants tested overall and 70% of those with a diagnostic result. Also, 7% of infants with a negative rWGS result and 23% with a variant of unknown significance (VUS) had a major change in management due to testing.Our study demonstrates that the implementation of rWGS is feasible across diverse institutions and provides additional evidence to support the clinical utility of rWGS in a demographically representative sample of admitted infants and includes assessment of the clinical impact of uncertain rWGS results in addition to both positive and negative results.